Buzzing Wild Bee Visits Enhance Seed Set in Eggplant, Solanum melongena - U. J. M. Shanika R. Jayasinghe; T. H. Saumya E. Silva; W. A. Inoka P. Karunaratne (Psyche: A Journal of Entomology)
Sixty percent of the angiosperms with poricidal anthers are buzz-pollinated by bees (Hymenoptera: Apoidea: Apiformes). Plant taxa with Solanum-type flowers have larger anthers and shorter filaments. Solanum melongena (Solanaceae) is more commonly and efficiently pollinated by buzz pollinators. The present study documented bees and their diurnal pattern of visitation to flowers, relationship between their handling time and flower age, and the effect of bee visits on fruit and seed set in S. melongena in two sites in Kandy District. Efficiency of buzz pollination over pollination in the absence of bees was determined using open buds and buds covered with pollinator exclusion bags. On average, 150 days were taken to complete the life cycle of Solanum melongena. Three buzzing bees and two nonbuzzing bees in site I and five buzzing bees and two nonbuzzing bees in site II were recorded. Handling time of Pachynomia sp. and Hoplonomia westwoodi indicates that bees spend more time at new flowers than at old flowers. Handling time is higher in the smaller bee, Pachynomia sp., than in the larger bee, H. westwoodi. Statistical data on pollinator exclusion experiment revealed that the fruit set and seed set of S. melongena are enhanced by buzz-pollinating bees.